Síntese de hidróxido duplo lamelar Mg-Al via rota mecanoquímica - Bento, Gabriel Soares (2022)
The synthesis of layered double hydroxides Mg-Al (LDH Mg-Al) via mechanochemical routes is reported. Manual grinding and horizontal ball milling were using as precursors aluminum hydroxide and magnesium oxide. The parameters of grinding time and addition of water were analyzed. The obtained products were characterized by x-ray diffraction (XRD), fourier transform infared (FTIR), scanning electron microscopy (SEM), transmission electron microscopy (MET), termogravimetry (TG/DTG), electron diffraction (SAED) and in addition, three samples were selected to be submitted to tests of adsorption of humic acid by UV-Visible spectroscopy. A green synthesis was promoted due to the non-use of water in large quantities. Manual grinding samples obtained at 10 minutes of grinding with 2.0 mL of water added positive results simlarly to samples synthesized with the aid of an aging stage. The formation of HDL phases were also observed in samples obtained in 80 hours and 100 hours of grinding with horizontal ball milling, while the presence of crystalline phases of MgO precursor was reduced by around 40 hours of grinding. Samples obtained at 10 minutes of manual dry grinding showed intermediate phases, indicating the importance of adding water in the synthesis process. The formation of the LDH product obtained manually with the addition of water even if in small quantities discards the use of traditional methods involving solutions, such as coprecipitation for example. FTIR bands, MET and SEM microscopies, electron diffraction and TG/DTG curves complemented the discussion about x-ray diffraction, with emphasis on the FTIR that presented information to some free (OH) groups – no participation in hydrogen bonds – characteristics of Al(OH)3 and the amorphization behavior of this reagent used as a precursor. Adsorption testes revealed that one of the products obtained by manual milling showed excellent humic acid adsorption property when compared to other samples, one obtained by co-precipitation and the other commercial.